Development of a Polymerase Spiral Reaction-Based Isothermal Assay for Rapid Identification of Thrips palmi - Jangra, Sumit; Ghosh, Amalendu; Mukherjee, Sunil; Baranwal, Virendra Kumar; Dietzgen, Ralf G. (Frontiers in Molecular Biosciences, 2022)
Thrips cause considerable economic losses to a wide range of food, feed, and forest crops. They also transmit several plant viruses. Being cryptic, it is often difficult to distinguish thrips species in crops and large consignments by conventional methods. Melon thrips (Thrips palmi Karny, Thysanoptera: Thripidae) is an invasive insect pest of vegetables, legumes, and ornamentals besides being vector to several viruses. It poses a threat to domestic and international plant biosecurity and can invade and establish in new areas. Here, we report a polymerase spiral reaction (PSR)-based isothermal assay for rapid, sensitive, specific, low-cost, and on-site detection of T. palmi. To the best of our knowledge, this is the first application of PSR in the identification of any insect species. A primer pair designed based on 3′-polymorphism of mtCOIII region can specifically identify T. palmi without any cross-reactivity with predominant thrips species. The assay uses crude lysate of a single thrips saving time and reagents involved in nucleic acid extraction. The presence of T. palmi is visualized by the appearance of bright fluorescence under ultraviolet light or a change in reaction color thus avoiding gel electrophoresis steps. The entire process can be completed in 70 min on-site using only an ordinary water bath. The assay is sensitive to detecting as little as 50 attograms of T. palmi template. The assay was validated with known thrips specimens and found to be efficient in diagnosing T. palmi under natural conditions. The described method will be useful for non-expert personnel to detect an early infestation, accidental introduction to a new area, restrict the spread of diseases and formulate appropriate management strategies.